Expression of Reverse Transcriptase Genes in Fulvia fulva - McHale, M.; Roberts, I.; Talbot, N.; Oliver, Richard (1989)
Antibodies raised against intercellular fluid antigens isolated from diseased tomato leaves have revealed that the fungal pathogen Fulvia fulva expresses genes for a fungal reverse transcriptase (RNA-dependent DNA polymerase). This enzyme is required for the replication of retroviruses and retroviral-like transposable elements and could provide a mechanism for increasing the mutation rate of fungal pathogens, perhaps explaining their ability to evolve new races rapidly. We report here the DNA sequence of a 225-bp clone from a ?gt11 genomic library of F. fulva. This clone, designated P5, exhibits a high degree of sequence homology with the reverse transcriptase (pol) gene of the Drosophila melanogaster copia-like retrotransponson 17.6. Southern blot analysis of genomic DNA of F. fulva showed that P5-related sequences are moderately reiterated with 30-100 copies, some of which exhibit restriction fragment length polymorphism in different races of the pathogen. Western blot analysis of extracts from F. fulvawith antibodies raised to purified reverse transcriptase (from human immunodeficiency virus-1) revealed immunoreactive proteins. Reverse transcriptase previously has been detected in a variety of organisms including yeast, insects, protozoa, and mammals, but to our knowledge, this is the first report of its occurrence in filamentous fungi.